DISPERSION ELECTROMAGNETIC RADIATION SHIELDS FOR THE INFORMATION PROTECTION SYSTEMS - M. A. Vilkotski; L. M. Lynkou; F. A. Saad (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The possibilities of using dispersion shields which are planar structures formed by resonant elements of wire and slot-type against information leakage via electromagnetic emanation. Such shields can have a large variance in the transmission coefficient of the complex plane, which leads to destruction of the structure of pulsed broadband signals. However, such structures may have narrow frequency bands in which the dispersion characteristics allow signal transmission implementation either creation of frequency space barrier in the narrow band.